2005
DOI: 10.1021/jm049609r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure−Activity Relationships, and Biological Evaluation of Fatty Alcohol Phosphates as Lysophosphatidic Acid Receptor Ligands, Activators of PPARγ, and Inhibitors of Autotaxin

Abstract: We previously reported that fatty alcohol phosphates (FAP) represent a minimal pharmacophore required to interact with lysophosphatidic acid (LPA) receptors. To improve the activity of the first-generation saturated FAP series, a structure−activity relationship (SAR) study was carried out that includes modifications to the headgroup and alkyl side chain of the FAP pharmacophore. A series of unsaturated (C10−C18) FAP, headgroup-modified hydrolytically stable saturated (C10−C18) alkyl phosphonates, and saturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 41 publications
3
121
0
Order By: Relevance
“…57) The involvement of LPA receptors was confirmed with oleyl thiophosphate, which is a partial agonist for LPA 1 and LPA 3 , and a potent and full agonist for LPA 2 . 35) Our finding that oleyl thiophosphate could suppress CCL21-induced chemotaxis of splenic lymphocytes is further evidence of the involvement of some LPA receptors in the regulation of chemokine signaling. To determine which receptors are responsible for this effect, further studies are required.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…57) The involvement of LPA receptors was confirmed with oleyl thiophosphate, which is a partial agonist for LPA 1 and LPA 3 , and a potent and full agonist for LPA 2 . 35) Our finding that oleyl thiophosphate could suppress CCL21-induced chemotaxis of splenic lymphocytes is further evidence of the involvement of some LPA receptors in the regulation of chemokine signaling. To determine which receptors are responsible for this effect, further studies are required.…”
Section: Discussionsupporting
confidence: 54%
“…35) We observed that oleyl thiophosphate inhibited CCL21-induced lymphocyte chemotaxis at 0.1 mM (Fig. 3).…”
Section: And B Cellsmentioning
confidence: 69%
“…[29] Briefly, rat hepatoma RH7777 cells stably expressing human LPA 1 , LPA 2 , or LPA 3 , and CHO cells stably expressing LPA 4 , were loaded with Fura-2 AM (Molecular Probes). Using a FLEXStation (Molecular Devices, Sunnyvale, CA), changes in intracellular Ca 2+ concentration were monitored.…”
Section: Receptor Activation Using Ca 2+ Mobilization Assaymentioning
confidence: 99%
“…Several groups have reported the characterization of the LPA agonists and antagonists. [20][21][22][23][24][25][26][27][28][29] Appropriately validated compounds are essential to advance in vivo studies, particularly in view of potential off-target effects. The development of more selective, more stable, more potent, and more druglike agonists and antagonists is eagerly awaited, and is the bottleneck in therapeutic exploration.…”
Section: Introductionmentioning
confidence: 99%
“…The compound classes shown or predicted here to be PPAR␥ ligands, sulfonylureas [4, RЈ ϭ (substituted) amino] and N-acylsulfonamides [4, RЈ ϭ (substituted) alkyl or aryl, pK a values of ϳ5] smoothly fit into this picture. Other compound classes exhibiting similar or higher acidity and similar H acceptor ability of their anions were recently shown to be PPAR␥ ligands [oxazolidinediones (Momose et al, 2002b), tetrazoles (Momose et al, 2002a), phosphates, and thiophosphates (Durgam et al, 2005)]. Circumstantial evidence for our views is provided by the observation that the succinimide analog of an antihyperglycemic thiazolidinedione (2, but S replaced by CH 2 , pK a 9.7), as well as the corresponding N-methylthiazolidinedione, are both inactive (Cantello et al, 1994).…”
Section: Discussionmentioning
confidence: 67%